An acute case of iron toxicity on newborn piglets from Vitamin E/Se deficient sows - Velásquez, Jaime I.; Aranzazu, Diego (Revista Colombiana de Ciencias Pecuarias, 2016)
Summary A 270 sow herd cut down feed costs by lowering Vitamin E and Selenium that was changed from an organic to an inorganic form. Several months later two week newborn batches were affected by a deadly hemorragic clinical entity developed 6 hours after a normal iron dextran injection. The brand of the iron came from a 2 year supplier, a world renown manufacturer. A therapeutic diagnosis was applied satisfactorily. Key words: deficient, piglets, selenium, sows, toxicity, vitamin E. Resumen Un hato de 270 cerdas bajó el costo de alimento, mediante el cambio por reducción vitamina E y selenio de forma orgánica a una inorgánica. Varios meses después, los lechones recién nacidos de dos semanas del parto, se afectaron de una entidad mortal hemorrágica, 6 horas después de la inyección con hierro dextran. El producto provenía de un proveedor de dos años, reconocido mundialmente. Se aplicó un diagnóstico terapéutico con resultados satisfactorios. Palabras clave: cerdas, deficiente, lechones, selenio, toxicidad, vitamina E.